A Role for All-Trans-Retinoic Acid in the Early Steps of Lymphatic Vasculature Development - Marino, Daniela (S. Karger AG, 2011)
The molecular mechanisms that regulate the earliest steps of lymphatic vascular system development are unknown. To identify regulators of lymphatic competence and commitment, we used an in vitro vascular assay with mouse embryonic stem cell-derived embryoid bodies (EBs). We found that incubation with retinoic acid (RA) and, more potently, with RA in combination with cAMP, induced the expression of the lymphatic competence marker LYVE-1 in the vascular structures of the EBs. This effect was dependent on RA receptor (RAR)-α and protein kinase A signaling. RA-cAMP incubation also promoted the development of CD31+/LYVE-1+/Prox1+ cell clusters. In situ studies revealed that RAR-α is expressed by endothelial cells of the cardinal vein in ED 9.5–11.5 mouse embryos. Timed exposure of mouse and Xenopus embryos to excess of RA upregulated LYVE-1 and VEGFR-3 on embryonic veins and increased formation of Prox1-positive lymphatic progenitors. These findings indicate that RA signaling mediates the earliest steps of lymphatic vasculature development.